Cortical spreading depression and mitochondrial dysfunction with aging: lessons from ethanol abuse - Barreto, George E. (2014)
Chronic consumption of ethanol has a damaging effect in various organs and metabolic functions, including liver, kidney, heart, pancreas, and brain (Sun and Sun, 2001; Bezerra Rde et al., 2005). Additionally, it has been shown that both the acute and chronic ethanol intake induce alteration in voltage-gated channels causing behavioral and electrophysiological changes in the brain (Little, 1999). In the last few years, the effect of ethanol in the electrophysiological phenomenon, known as cortical spreading depression (CSD), has been widely assessed (Sonn and Mayevsky, 2001; Bezerra Rde et al., 2005; Abadie-Guedes et al., 2008) as an important model to predict the damaging effects of ethanol in both young and aged brains.